Immune biomarkers in circulating cells of NSCLC patients can effectively evaluate the efficacy of chemotherapy combined with anti-PD-1 therapy - Cao, Jing; Zhang, Yuehua; Guo, Shenghu; Wu, Zheng; Guo, Xiaojin; Zhang, Rongze; Zhang, Lei; Liu, Ya; Li, Xing; Yang, Chunwang; He, Dongwei; Bai, Lu; et al. (Frontiers in Immunology, 2025)
IntroductionThe application of programmed cell death protein 1 (PD-1) antibodies has brought significant benefits to patients with non-small cell lung cancer (NSCLC). However, not all patients respond to PD-1 immune therapy. The aim of this study was to identify response biomarkers to predict the efficacy of chemotherapy combined with anti-PD-1 therapy in NSCLC patients.MethodsThirty-two NSCLC patients receiving chemotherapy combined with anti-PD-1 therapy were recruited, and peripheral blood samples were collected before and after treatment. Flow cytometry was used to detect the proportions of circulating T-cell subsets, and cytokines in the blood serum were detected via ELISA.ResultsThe results revealed that, among the CR/PR group (CR, complete response; PR, partial response; n = 22), the proportions of CD3+TIM-3+PD-1+, CD3+CD4+TIM-3+PD-1+, and CD3+CD8+TIM-3+PD-1+, CD3+γδT+PD-1+, CD3+γδT+Vδ1+PD-1+, and CD3+γδT+Vδ2+PD-1+T cells were lower after treatment, with no significant differences found between the stable disease (SD) and progressive disease (PD) groups (n = 10). Some proinflammatory cytokines are highly expressed in patients with NSCLC.DiscussionThis study suggests that monitoring changes in immune biomarkers in the circulating cells of NSCLC patients may help differentiate CR/PR patients from SD/PD patients, providing a potential new approach for assessing the efficacy of chemotherapy combined with anti-PD-1 therapy.